Studi perencanaan overlay Jalan Ruas Kambuaya– Kumurkek Kab. Maybrat dengan tebal perkerasan lentur menggunakan metode Manual Desain Perkerasan Jalan (MDP) 2017 - Malibela, Thedie; Maryam, St; Bulqis, Bulqis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Road pavement refers to a layer situated between the subgrade dirt layer and the wheels of vehicles. It seeks to offer transportation services while ensuring that no substantial damage is anticipated during its operation. The road from Kambuaya to Kumurkek, recognized as the principal thoroughfare in West Papua, is a crucial infrastructure for enhancing the local economy. Consequently, to attain this enhancement, it is essential to evaluate and refine the current road pavement. The flexible pavement is defined as a pavement composed of a paved mixture for the surface layer and granular material for the underneath layer. The pavement layer possesses elasticity that enhances vehicle comfort during transit. Moreover, the 2017 MDP approach has been employed to assess the thickness of road pavement, contributing to the improvement of road performance while addressing the issues and impediments to asset performance in Indonesia. The Directorate General of Highways and Construction Development has established technical criteria for the restoration of severely damaged roadways. The specification encompasses a series of pavement layers designated for all National roads. This research employed a quantitative methodology, utilizing both primary and secondary data, and calculated pavement thickness based on the 2017 MDP. The findings indicated structural degradation on the Kambuaya to Kumurkek route, specifically in section 6, necessitating an additional structural overlay layer triggered by an IRI score of 2. Furthermore, it necessitated an extra layer thickness of 60 mm and mandated repair in sections 7 and 8 of the Kambuaya-Kumurkek road section, triggered by an IRI value of 3. Furthermore, section 9 requires non-structural overlay management due to an IRI value of 1, whereas the preceding section, section 10, necessitated reconstruction owing to an IRI value of 3 following the structural number assessment. This research suggests that the treatment constitutes a significant rehabilitation..